Effect of PCSK9 inhibition with evolocumab on lipoprotein subfractions in familial dysbetalipoproteinemia (type III hyperlipidemia) - Waldmann, Elisa; Wu, Liya; Busygina, Kristina; Altenhofer, Julia; Henze, Kerstin; Folwaczny, Alexander; Parhofer, Klaus G. (PLOS ONE, 2022)
Background and aims Familial dysbetalipoproteinemia (FDBL) is a rare inborn lipid disorder characterized by the formation of abnormal triglyceride- and cholesterol-rich lipoproteins (remnant particles). Patients with FDBL have a high risk for atherosclerotic disease. The effect of PCSK9 inhibition on lipoproteins and its subfractions has not been evaluated in FDBL. Methods Three patients (65±7 years, 23±3 kg/m2, 2 females) with FDBL (diagnosed by isoelectrofocusing) and atherosclerosis (coronary and/or cerebro-vascular and/or peripheral arterial disease) resistant or intolerant to statin and fibrate therapy received evolocumab (140mg every 14 days). In addition to a fasting lipid profile (preparative ultracentrifugation), apoB and cholesterol concentrations were determined in 15 lipoprotein-subfractions (density gradient ultracentrifugation; d 1.006–1.21g/ml) before and after 12 weeks of evolocumab treatment. Patients with LDL-hypercholesterolemia (n = 8, 56±8 years, 31±7 kg/m2) and mixed hyperlipidemia (n = 5, 68±12 years, 30±1 kg/m2) also receiving evolocumab for 12 weeks were used for comparison. Results All patients tolerated PCSK9 inhibition well. PCSK9 inhibitors reduced cholesterol (29–37%), non-HDL-cholesterol (36–50%) and apoB (40–52%) in all patient groups including FDBL. In FDBL, PCSK9 inhibition reduced VLDL-cholesterol and the concentration of apoB containing lipoproteins throughout the whole density spectrum (VLDL, IDL, remnants, LDL). Lipoprotein(a) was decreased in all patient groups to a similar extent. Conclusions This indicates that the dominant fraction of apoB-containing lipoproteins is reduced with PCSK9 inhibition, i.e. LDL in hypercholesterolemia and mixed hyperlipidemia, and cholesterol-rich VLDL, remnants and LDL in FDBL. PCSK9 inhibition may be a treatment option in patients with FDBL resistant or intolerant to statin and/or fibrate therapy.